PENGARUH SELF CONFIDENCE SISWA SMP TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Indiraningrum Pratiwi; Dwi Yulianti; Pamila Malinda; Pipit Pitriyani; Mira Siti Hajar; Wahyu Hidayat (IKIP Siliwangi, 2018)
This research aims to know the influence of student’s self-confidence against the ability of mathematical creative thinking of students. Methods used correlational with quantitative approach. Samples taken is as much as 30 students are subjected to an SMP in the city of Cimahi. The instruments used in this research consists of a test and non-test. The results of this research are the self-confidence of students have a positive effect on the ability of mathematical creative thinking of the students of 10.9% and 89.1% influenced by factors other than the self-confidence.